Investigation the role of CD24 in metastatic colorectal cancer - Alsulaiman, Abdullah (2018)
CD24 is a small (81 amino acids) GPI anchored protein which is involved in promoting cell motility and stemness and may be a part of the metastatic process. It is a heavily glycosylated molecule and contains numerous O-glycosylation sites together with two N-glycosylation sites. N-glycosylation is thought to be important in protein function, and therefore, the aim of this study is to (a) investigate the importance of N-glycosylation in the function of CD24, (b) identify other potentially functional sites in CD24 by deletion mapping, (c) define downstream targets of CD24, and (d) identify the extrinsic signals of which activate CD24.